Sergeant on stamp duties - Sims, Bernard John.; Hodgson, J. B.; Tavaré, A. K. (London : Butterworths, 1968)
The subject of relief from stamp duty on company reorganizations and in connection with transfers between inter-connected companies continues to be of increasing importance and loan capital duty has come into greater prominence. All these topics are treated fully in the text.
First ed. published in 1939 under title: The law of stamp duties.
Includes index.
ne 22/01/2019
Loans
Keywords: Stamp duties